(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
In the present study best suitable explant for encapsulation and effect of nutrient composition of alginate matrix on regrowth performance of encapsulated explants of endangered C. spiralis and C. pusilla were studied. Among all the explants tested, good sprouting frequency was observed with shoot tips in both the species. Where as, multiple shoot induction with maximum shoot length was noticed with nodes. Sprouting frequency and viability of explants were reported in both the encapsulation mixtures tested. But, the significant increase in sprouting percentage, maximum number of shoots formed for each encapsulated explant and maximum shoot length were achieved with the encapsulation matrix prepared with Murashige and Skoog (MS) + 3 mg/L Benzyle amino purine (BAP) + 3 % sucrose + 3 % sodium alginate in both the species C. spiralis and C. pusilla. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15412 Bangladesh J. Sci. Ind. Res. 48(1), 39-42, 2013